2016
DOI: 10.3839/jabc.2016.027
|View full text |Cite
|
Sign up to set email alerts
|

EndophyticBacillus subtilisMJMP2 from Kimchi inhibitsXanthomonas oryzaepv.oryzae, the pathogen of Rice bacterial blight disease

Abstract: An endophytic bacterial strain was isolated from kimchi, a Korean traditional fermented Brassica campestris and identified as Bacillus subtilis MJMP2 based on the 16S rRNA sequence. This strain showed strong antagonistic activity against Xanthomonas oryzae pv. oryzae (Xoo) KACC10331, the pathogen of bacterial rice blight disease, as well as activity against some other rice phytopathogenic fungi. The active compound was purified through size-exclusion chromatography and preparative High-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Iturins are a class of lipopeptides produced by B. subtilis and B. amyloliquefasciens that are widely studied for their antiproliferative and antimicrobial properties. However, studies on antimicrobial activity of iturins are restricted to the biological control of phytopathogens, including phytopathogenic fungi and bacteria (Etchegaray et al 2008 ; Arrebola et al 2010 ; Zeriouh et al 2011 ; Gong et al 2015 ; Mora et al 2015 ; Yamamoto et al 2015 ; Cheng et al 2016 ). To date, the number of studies that explore the therapeutic application of iturins is very low (Patel et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Iturins are a class of lipopeptides produced by B. subtilis and B. amyloliquefasciens that are widely studied for their antiproliferative and antimicrobial properties. However, studies on antimicrobial activity of iturins are restricted to the biological control of phytopathogens, including phytopathogenic fungi and bacteria (Etchegaray et al 2008 ; Arrebola et al 2010 ; Zeriouh et al 2011 ; Gong et al 2015 ; Mora et al 2015 ; Yamamoto et al 2015 ; Cheng et al 2016 ). To date, the number of studies that explore the therapeutic application of iturins is very low (Patel et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the most common solution is pesticides, but this pollutes the water, soil and air environments (Kim et al, 2017). On the other hand, the most researched solution is using Xoo amensalism bacteria such as Bacillus spp., Actinomyces and Pseudomonas aeruginosa (Hop et al, 2014;Cheng et al, 2016;Yasmin et al, 2017). However, because the microorganisms used in biological control only inhibit the reproduction of pathogenic microorganisms and cannot eliminate Xoo directly, their efficiency is lower than expected (Adachi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms induced the plant defense response termed induced systemic resistance through microbeassociated molecular pattern triggered immunity in crop plants (Yang et al, 2009). Previous findings indicated that Bacillus and Pseudomonas strains have a greater capacity to produce compounds such as lipopeptides and secondary metabolites, which manifest antimicrobial activities against plant pathogens (Cheng et al, 2016). Similarly, the plant extracts have been effectively utilized for the plant disease management merely with the wider mechanism of action including the induced the plant defense to suppress the growth of the pathogen, showed a direct effect on the pathogen and use of plant extract are cheap, locally available, non-toxic and biodegradable.…”
Section: Introductionmentioning
confidence: 99%